Application of the Principles of Islamic Civil Law in Small and Medium Business Partnerships - Sunarto, Atika; Muhammad Ali Adnan; Azizan Khair (Nurani, 2025)
Partnerships in Small and Medium Enterprises (SMEs) in Indonesia often encounter challenges in adhering to Islamic principles such as syirkah (partnership), justice, transparency, and social responsibility. Therefore, there needs to be a commitment from the government, financial institutions and business actors to encourage the implementation of Islamic law values ​​in business practices. This study aims to find solutions in implementing these principles in Small and Medium Enterprise partnerships in Indonesia. The methods employed include a qualitative approach, utilizing in-depth interviews and case studies to gain a deeper understanding of current practices and the challenges faced. The research results show that although Islamic legal principles have great potential to form fair and sustainable partnerships, their implementation is often not optimal. The principles of syirkah are often not applied fairly, justice in the distribution of profits is often hampered by power, transparency is often ignored, and social responsibility is often given little attention. The conclusion of this research is that to increase the application of Islamic legal principles in Small and Medium Enterprise partnerships, greater efforts are needed in regulatory reform, increased education, and support from sharia financial institutions. This approach aims to promote fairer and more sustainable business practices while ensuring that the principles of Islamic law are effectively implemented within the context of Small and Medium Enterprise partnerships.